Europæerne: FIX&FOXYs postdramatiske tilgang til klassikerne - Thygesen, Mads (Peripeti, 2022)
Europæerne. En postdramatisk tilgang til klassikerne by Mads Thygesen. How did the staging of The Europeans exploit classics as a tool to intervene and mix in a current historical and political context? The common denominator for the work was European wars as a dramatic focal point. The article discusses how this performance illuminates the seed of FIX&FOXY’s poetics and conceptual thinking from 2005.